1995
DOI: 10.3354/meps121191
|View full text |Cite
|
Sign up to set email alerts
|

Effects of soft corals on scleractinian coral recruitment. I:Directional allelopathy and inhibition of settlement

Abstract: Experiments were performed on the Great Barrier Reef, at Orpheus lsland (18" 40'S, 145" 30' E) and Lizard Island (14" 41' S, 145" 28' E), Australia, to examine allelopathic effects of soft corals on the larval recruitment of scleractinian corals. Ceramic tiles were used as settlement plates and arranged around the soft corals Sinularia flexibilis (Quoy & Gaimard) and Sarcophyton glaucurn (Quoy & Gaimard), serving as treatments. One control consisted of stacks of settlement plates uninfluenced by any organism, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(68 citation statements)
references
References 31 publications
2
66
0
Order By: Relevance
“…Settlement tiles, deployed in 3-4 m depth along the reef edge, were revisited every 4 months in order to detect changes between wet, transition and dry seasons. Terracotta tiles (Harriott and Fisk, 1987;Maida et al, 1995;Dunstan and Johnson, 1998) (15 Â 15 cm) were connected pairwise by a stainless steel bolt, with the unglazed faces exposed and the glazed faces touching each other (n = 16 tile pairs for each site). The bolt holding the tiles was fixed at an angle of 45°on dead coral boulders.…”
Section: Coral Recruitmentmentioning
confidence: 99%
“…Settlement tiles, deployed in 3-4 m depth along the reef edge, were revisited every 4 months in order to detect changes between wet, transition and dry seasons. Terracotta tiles (Harriott and Fisk, 1987;Maida et al, 1995;Dunstan and Johnson, 1998) (15 Â 15 cm) were connected pairwise by a stainless steel bolt, with the unglazed faces exposed and the glazed faces touching each other (n = 16 tile pairs for each site). The bolt holding the tiles was fixed at an angle of 45°on dead coral boulders.…”
Section: Coral Recruitmentmentioning
confidence: 99%
“…on the brooded planulae of Acropora palifera and Stylophora pistillata and suggested allelopathy as the mechanism. Similarly, Maida et al (1995) showed allelopathic effects for 2 species of soft corals on scleractinian recruitment. However, an alternative to allelopathy is the hypothesis that pathogens associated with the algae are responsible for the observed negative effect (Nugues et al 2004b).…”
Section: P I N N a T I F I D A C P O I T E A U I L P O L Y C mentioning
confidence: 99%
“…Having the structural flexibility to tolerate this type of condition, soft corals are able to thrive on the exposed side of reefs (Hong and Sasekumar, 1981). The other factor that influences the growth of soft corals is the ability to inhibit the growth of their adjacent hard corals by releasing toxins (Maida et al, 1995;Fabricius, 1998). Hence, soft corals are able to grow and compete with hard corals to dominate certain areas of the reefs.…”
Section: Coral Composition At Tioman Islandmentioning
confidence: 99%